The Peopling and Migration History of the Natives in Peninsular Malaysia and Borneo: A Glimpse on the Studies Over the Past 100 years - Hoh, Boon-Peng; Deng, Lian; Xu, Shuhua (Frontiers in Genetics, 2022)
Southeast Asia (SEA) has one of the longest records of modern human habitation out-of-Africa. Located at the crossroad of the mainland and islands of SEA, Peninsular Malaysia is an important piece of puzzle to the map of peopling and migration history in Asia, a question that is of interest for many anthropologists, archeologists, and human population geneticists. This review synopsizes what had been found on the population genetics of the natives from Peninsular Malaysia and Borneo over the past century. The study of indigenous populations in Malaysia was prompted by the intention to classify ‘race’ in the 19th century. The classifications, not so much on genetics, were based on physical appearance, along with language, culture, and socio-economic activities. Decades after World War II saw vast changes in the studies of indigenous populations – blood-group anthropology took over as the new way of testing racial provenance. Subsequently, isozyme variations were studied. The availability of DNA markers in the 1990s–2000s especially human mtDNA and molecular clocking, suggested that the indigenous populations may have inhabited in Peninsular Malaysia between 45-60 kya. The HUGO Pan-Asian SNP Consortium revealed an early ‘Southern Route’ migration out-of-Africa, with subsequent multiple migration events resulting in complex genetic admixtures in SEA. Using whole-genome genotyping data, we revealed that the Borneo natives exhibited close genetic affinity to the Taiwanese aborigines, supporting the Austronesian expansion hypothesis. Recent ancient human genome analyses suggest a close genetic link between the indigenous populations and the ancient group from the Hoabihnian culture and Neolithic period provides further insights to dating the peopling history in this landmass. Whilst speedy advancement has been made over the last decade, many questions remain unanswered. We provide some insights into the ‘missing puzzles’ of the peopling history in SEA that remained to be filled. Challenges of studying the poplation genetics of natives will also be elaborated. We conclude our review by reiterating the importance of unveiling migration history and genetic diversity of the indigenous populations in complementing the catalog for human genome variation and providing a stepping stone towards comprehending disease evolution and etiology